CONSTRUCTIVE ACTIVITIES TO THE SAMANID RULERS - Umarov Bakhtishod (Western European Studies, 2024)
In the IX-X centuries in Maverannahr and Khorasan with the coming to power of the Samanid dynasty all spheres began to develop rapidly. Establishment of close ties with scientific centres of the caliphate, development of trade and crafts directly improved the economic situation of the country. As a result of the growth of trade and cultural relations in such cities as Bukhara, Samarkand, Fergana, Shash, Merv and Nishapur, madrasas were built and they became big cities of the Muslim world. As the topic is very topical, this article is about analysing the creative activity of Samanid rulers.
Keywords: Samanid ruler; Ismail Samani; mosque